Investigation of Antibacterial Activity of Pimpinella affinis Leaves Against E. coli and S. aureus and Separation of Active Fractions - Yaghoub Sarrafi; Hadis Tavahodi; Hossein Dehghan (Institue of Medicinal Plants, ACECR, 2017)
Background: Pimpinella affinis (Apiaceae family) is a vegetable in the north of Iran. Objective: This study was conducted to investigate antibacterial activity of Pimpinella affinis (against E. coli and S. aureus) and separate its active fractions. Methods: Antibacterial activities of n-hexane, ethyl acetate and methanol extracts of leaves of P. affinis (against E. coli and S. aureus) were measured using broth microdilution method in MIC. Subsequently, the ethyl acetate extract was separated in to 29 fractions using column chromatography and thin layer chromatography (TLC). Also, antibacterial activities of the fractions have been measured. Results: According to the results, among the extracts, ethyl acetate extract showed the best activities against E. coli and S. aureus (MICs=1.0 and 2.0 mg/ml, respectively). Also, among the obtained fractions from ethyl acetate extract, F3-F5, F8 and F9 showed best inhibitory activities (MIC=5.0 μg/ml, P<0.05) compared with that of the chloramphenicol (MIC=1.0 μg/ml, P<0.01). All of the results have p-values less than 0.05. Conclusion: The results showed that the Gram positive S. aureus is more sensitive to the extracts than the Gram negative E. coli. Also, partitioning of the ethyl acetate extract leaded to obtain antibacterial fractions (F3-F5, F8 and F9) with 200-fold more active than the ethyl acetate extract.